Research Trends of Problem Based Learning (PBL) Model in Science Courses in Universities - Roza, Media; Azhar, Minda; Yohandri, Yohandri; Arsih, Fitri (AT-TA'LIM, 2023)
The PBL model has relevance and potential in developing 21st-century skills. This study uses the Systematic Literature Review method to identify PBL research trends in science courses at universities. A literature search using the app Publish or Perish with the Scopus database and data from journals indexed by SINTA (Science and Technology Index) in the last 10 years, from 2012 to 2021. In this study, there are 32 articles about PBL research in science lectures, including physics, chemistry, biology, and natural science.Â  The trend seen is a rise in publications addressing various facets of critical thinking abilities. Among research publications, quantitative research is the most common type. Quasi-Experimental designs are most often chosen by researchers, while RD designs are still little used. Chemistry is a subject that is most often chosen as a research subject. Meanwhile, the test is the most commonly used instrument for collecting data on 21st-century student skills